Enabling the content dissemination through caching in the state-of-the-art sustainable information and communication technologies. (October 2020) - Naeem, Muhammad Ali; Ali, Rashid; Alazab, Mamoun; Meng, Yahui; Zikria, Yousaf Bin
Abstract: The involvement of Information and Communication Technologies (ICT) has become essential for daily lives because their usages are broadly acceptable to meet the requirements of the modern era. The present communication architecture is depending on an out paradigm due to which similar data needs to send several times over the Internet. Therefore, global communication technologies are facing several critical issues related to modern ICT-based technologies such as link load, network congestion, unnecessary usage of resources, and server load. Recently, a new cache-based communication technology called Named Data Networking (NDN) emerged to overcome these issues. In NDN, network routers are equipped with a cache that provides storage to the disseminated content for caching at intermediate routers to fulfill the subsequent consumers' requirements. The caching strategy modifies communication services. Therefore, in this study, an innovative cache deployment strategy named as Most Interested Content Caching (MICC) is proposed to enhance the content dissemination by caching the transmitted content at appropriate locations. The MICC extensively and comparatively is evaluated by comparing its performance with existing NDN-based caching mechanisms. Hence, MICC is performed better with regards to the cache hit, stretch, eviction, and diversity. Consequently, the MICC will be efficient in enhancing the ICT-based communications approaches.